Search for new physics in final states with a lepton and missing transverse energy in pp collisions at the LHC - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2013)
This Letter describes the search for an enhanced production rate of events with a charged lepton and a neutrino in high-energy pp collisions at the LHC. The analysis uses data collected with the CMS detector, with an integrated luminosity of 5.0 fb-1 at √s=7 TeV, and a further 3.7 fb -1 at √s=8 TeV. No evidence is found for an excess. The results are interpreted in terms of limits on a heavy charged gauge boson (W ′) in the sequential standard model, a split universal extra dimension model, and contact interactions in the helicity-nonconserving model. For the last, values of the binding energy below 10.5 (8.8) TeV in the electron (muon) channel are excluded at a 95% confidence level. Interpreting the ℓν final state in terms of a heavy W′ with standard model couplings, masses below 2.90 TeV are excluded. © 2013 CERN.